2023
DOI: 10.1001/jamaoncol.2022.7762
|View full text |Cite
|
Sign up to set email alerts
|

First-line Systemic Treatment Options for Metastatic Castration-Sensitive Prostate Cancer

Abstract: ImportanceThe effectiveness of triplet therapy compared with androgen pathway inhibitor (API) doublets in a heterogeneous patient population with metastatic castration-sensitive prostate cancer (mCSPC) is unknown.ObjectiveTo assess the comparative effectiveness of contemporary systemic treatment options for patients with mCSPC across clinically relevant subgroups.Data SourcesFor this systematic review and meta-analysis, Ovid MEDLINE and Embase were searched from each database’s inception (MEDLINE, 1946; Embase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 45 publications
0
23
0
1
Order By: Relevance
“…First, patient compliance with chronic corticosteroid use on the ADT, abiraterone 1,000 mg, and prednisone 10 mg regimen must be weighed, especially considering side effects such as immunosuppression, metabolic dysfunction, musculoskeletal weakness, and psychological disturbance. Second, individual trials of triplet therapy regimens such as ADT, docetaxel, and darolutamide have demonstrated superior survival outcomes compared to some doublet regimens, 12,15 but questions linger regarding the impact that triplet therapy can have on patient health-related quality-of-life.…”
Section: Discussionmentioning
confidence: 99%
“…First, patient compliance with chronic corticosteroid use on the ADT, abiraterone 1,000 mg, and prednisone 10 mg regimen must be weighed, especially considering side effects such as immunosuppression, metabolic dysfunction, musculoskeletal weakness, and psychological disturbance. Second, individual trials of triplet therapy regimens such as ADT, docetaxel, and darolutamide have demonstrated superior survival outcomes compared to some doublet regimens, 12,15 but questions linger regarding the impact that triplet therapy can have on patient health-related quality-of-life.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple systematic reviews and network meta-analyses have attempted to indirectly compare ADT + ARPI + docetaxel vs. ADT + ARPI based on the randomized trials reviewed and also including other RCTs studying ADT + ARPI vs. ADT alone [ 36 , 37 , 38 , 39 , 40 , 41 ]. These meta-analyses have shown mixed results regarding the benefit of docetaxel [ 36 , 37 , 38 , 40 , 41 ] in the context of inherent biases in the absence of individual patient data for definitive comparisons.…”
Section: Putting the Evidence Into Perspectivementioning
confidence: 99%
“…Multiple systematic reviews and network meta-analyses have attempted to indirectly compare ADT + ARPI + docetaxel vs. ADT + ARPI based on the randomized trials reviewed and also including other RCTs studying ADT + ARPI vs. ADT alone [ 36 , 37 , 38 , 39 , 40 , 41 ]. These meta-analyses have shown mixed results regarding the benefit of docetaxel [ 36 , 37 , 38 , 40 , 41 ] in the context of inherent biases in the absence of individual patient data for definitive comparisons. Although conducting a formal clinical trial to define the benefits of triplet therapy is ideal, there may be challenges to trial accrual given that ADT + ARPI is a highly effective backbone of treatment; many men with prostate cancer may be reluctant to be randomized to receive chemotherapy; and many clinicians may inherently favour either a doublet or triplet approach depending on patient characteristics and tumour risk factors.…”
Section: Putting the Evidence Into Perspectivementioning
confidence: 99%
“…In this issue of JAMA Oncology, Riaz et al report the results of a “living” systematic review using the aggregate data from 10 identified RCTs that collectively enrolled a total of 11 043 patients, including those in the previously cited studies, for inclusion in a meta-analysis and network meta-analysis . The direct comparative meta-analysis of 8 of these trials showed that an ARSI-based doublet was associated with a considerably greater OS benefit than a docetaxel-based doublet when compared with ADT alone.…”
mentioning
confidence: 99%